KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS IV SEKOLAH DASAR PADA PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE, THINK TALK WRITE, DAN TEAMS GAME TOURNAMENT - Saputra, Rivaldo Ihzan; Kesumawati, Nila; Sari, Eka Fitri Puspa (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to determine the differences in students’ mathematical communication skills among those taught using the cooperative learning models Think Pair Share (TPS), Think Talk Write (TTW), and Teams Games Tournament (TGT). This research employed an experimental design. The population consisted of all fourth-grade students of SD Negeri 148 Palembang in the 2024/2025 academic year, distributed across four classes. The research sample included classes IV.A, IV.B, and IV.C, selected using a cluster random sampling technique with a posttest-only control group design. Data were collected through a mathematical communication skills test. The results of the one-way ANOVA analysis showed no significant difference in students’ mathematical communication abilities among the three cooperative learning models. However, based on the posttest results, students who were taught using the Teams Games Tournament (TGT) model demonstrated slightly better mathematical communication skills compared to those in the TPS and TTW groups. Therefore, although statistically insignificant, the TGT model appeared to provide a more engaging learning environment that supports the improvement of students’ mathematical communication skills.